Enhanced Susceptibility to Breast Cancer in Korean Women With Elevated Serum Gamma-Glutamyltransferase Levels: A Nationwide Population-Based Cohort Study - Seol, Aeran; Wang, Wenyu; Kim, Se Ik; Han, Youngjin; Park, In Sil; Yoo, Juhwan; Jo, HyunA; Han, Kyung-Do; Song, Yong Sang (Frontiers in Oncology, 2021)
Background: The incidence of breast cancer has been gradually increasing in Korea. Recently, the elevated level of serum gamma-glutamyltransferase (GGT) has emerged to be associated with the development and progression of some malignancies. This study aimed to determine the effect of serum GGT levels on the risk of developing breast cancer in Korean women. Methods: We used National Health Insurance Service Health Checkup data to examine the association between serum GGT levels and breast cancer development in Korean women. Women aged 40 years or older who participated in the Korean National Health Screening Examination between January 2009 and December 2009 and who did not develop any cancer within 1-year post examination were included in this analysis (n = 3,109,506). Cox proportional hazard regression analysis was conducted to calculate hazard ratios (HRs) with 95% confidence intervals (CIs). Results: Overall, an elevated serum GGT level was associated with the increased risk of developing breast cancer; compared to the Q1 group, the Q4 group showed a significantly increased breast cancer risk (HR: 1.120,95% CI: 1.08－1.162). Such a relationship was stronger in post-menopausal women than pre-menopausal women (HR: 1.173, 95% CI: 1.107－1.243; HR: 1.070, 95% CI:1.019－1.124). Women with a high GGT level (Q4) were also at an increased risk of developing carcinoma in situ(CIS) (HR: 1.114, 95% CI: 1.04－1.192). In post-menopausal women, the Q4 group also exhibited higher CIS risk (HR: 1.266, 95% CI: 1.132－1.416). However, no significant difference in the risk of developing CIS was observed between the Q1 and Q4 groups in pre-menopausal women. Further analysis revealed that obese, post-menopausal women with a high GGT level (Q4) were associated with an increased risk of developing breast cancer (HR: 1.214, 95% CI: 1.125－1.31) and CIS (HR: 1.348, 95% CI: 1.159－1.569). Conclusions: Our study results demonstrate that increased serum GGT level is a risk factor for developing breast cancer. The post-menopausal women group with obesity and elevated serum GGT level showed the highest incidence of breast cancer. Thus, serum GGT concentration could be a novel and potential risk factor for breast cancer. Further validation in different ethnic groups would be warranted.